FEATURES OF THE COURSE, CLINICAL AND MORPHOLOGICAL CHARACTERISTICS OF AMELOBLASTOMA AND FIBROUS DYSPLASIA IN CHILDREN - Tkachenko, P.I.; Starchenko, I.I.; Bilokon, S.O.; Rezvina, K.Yu.; Popelo, Yu.V.; Dolenko, O.B.; Lokhmatova, N.M.; Korotych, N.N.; Bilokon, N.P. (World of Medicine and Biology, 2021)
The article highlights the features of the clinical course and morphological characteristics, diagnostic measures and treatment of children with ameloblastoma and fibrous dysplasia of the jaw bones. Absence of clear clinical manifestations, similarity of symptoms and nature of the course of ameloblastoma and fibrous dysplasia is inherent in all benign tumors of the maxillofacial area in children. They cause a significant percentage of diagnostic errors, making the issue of their differential diagnosis quite relevant for surgical dentistry and maxillofacial surgery.
Keywords: adamantinoma; fibrous dysplasia; benign tumors; children